STEK: A potential fast spectrum benchmark for fission product cross sections - van der Marck, Steven; Koning, Arjan (Frontiers in Energy Research, 2023)
The reactivity worth of many fission product samples was measured in fast spectrum conditions in the STEK facility during the early 1970s. These results were then used to improve and validate nuclear data evaluations for fission products, but in the last 2 decades STEK has not been used: the nuclear data evaluations for fission products in the current versions of libraries like ENDF/B or JEFF have not been tested against STEK results. Here we argue that the STEK data are still valuable, because there is no other data set that can replace them, and the interest in fast spectrum conditions is picking up strongly of late. It should be considered to evaluate whether a benchmark can be defined for the International Reactor Physics Experiments Handbook.